2006
DOI: 10.1111/j.1460-9568.2006.04819.x
|View full text |Cite
|
Sign up to set email alerts
|

Emx2 in the developing hippocampal fissure region

Abstract: Mice deficient in transcription factor gene Emx2 show developmental alterations in the hippocampal dentate gyrus. Emx2, however, is also expressed in the region around the developing hippocampal fissure. The developing fissure contains a radial glial scaffolding, and is surrounded by the outer marginal zone and the dentate marginal zone, which become specifically colonized by neurons and differentiate into stratum lacunosum-moleculare and molecular layer of the dentate, respectively. In this study we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Especially prominent during the development of this region is the involvement of radial glia. Only a small number of factors have been identified that may be involved in the formation of the GFAP-positive glial scaffold during hippocampal development (Oldekamp et al, 2004;Zhou et al, 2004;Zhao et al, 2006). Here, we demonstrate that the maturation of distinct populations of radial glia are critical for certain aspects of DG formation, particularly the emergence of the hippocampal fissure and the migration of dentate granule cells.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Especially prominent during the development of this region is the involvement of radial glia. Only a small number of factors have been identified that may be involved in the formation of the GFAP-positive glial scaffold during hippocampal development (Oldekamp et al, 2004;Zhou et al, 2004;Zhao et al, 2006). Here, we demonstrate that the maturation of distinct populations of radial glia are critical for certain aspects of DG formation, particularly the emergence of the hippocampal fissure and the migration of dentate granule cells.…”
Section: Discussionmentioning
confidence: 60%
“…Foxg1, expressed very early in the telencephalon, most likely regulates cell fate upstream or independent of Nfib, as we did not detect any abnormality of the cortical hem of Nfib-deficient mice. Mice deficient in the transcription factors Emx2 and Pax6 have a similar hippocampal phenotype to the Nfib-deficient mice (Pellegrini et al, 1996;Tole et al, 2000;Oldekamp et al, 2004;Zhao et al, 2006). For instance, each mutant lacks a discernible hippocampal fissure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, Nfib knockout mice display hippocampal defects, including malformation of the dentate gyrus (SteelePerkins et al, 2005). A similar hippocampal phenotype has been observed in Emx2 knockout mice (Tole et al, 2000;Zhao et al, 2006), and microarray analysis in neural precursors identified Nfia as a downstream target of Emx2 (Gangemi et al, 2006). Another mouse mutant with similar hippocampal abnormalities is the LRP6 (low-density lipoprotein receptor-related protein)-deficient mice.…”
Section: Expression Of Nfi Proteins Throughout Hippocampal Developmentmentioning
confidence: 63%